2007
DOI: 10.1128/jcm.00729-07
|View full text |Cite
|
Sign up to set email alerts
|

Prophage Sequences Defining Hot Spots of Genome Variation inSalmonella entericaSerovar Typhimurium Can Be Used To Discriminate between Field Isolates

Abstract: Sixty-one Salmonella enterica serovar Typhimurium isolates of animal and human origin, matched by phage type, antimicrobial resistance pattern, and place of isolation, were analyzed by microbiological and molecular techniques, including pulsed-field gel electrophoresis (PFGE) and plasmid profiling. PFGE identified 10 profiles that clustered by phage type and antibiotic resistance pattern with human and animal isolates distributed among different PFGE profiles. Genomic DNA was purified from 23 representative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 28 publications
2
46
0
Order By: Relevance
“…The design and construction of the pan-Salmonella array was an extension of a previous array (Thomson et al, 2004), incorporating specific genes found in newly sequenced Salmonella genomes (Cooke et al, 2007). For each strain, genomic DNA was extracted from at least two cultures grown independently.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design and construction of the pan-Salmonella array was an extension of a previous array (Thomson et al, 2004), incorporating specific genes found in newly sequenced Salmonella genomes (Cooke et al, 2007). For each strain, genomic DNA was extracted from at least two cultures grown independently.…”
Section: Methodsmentioning
confidence: 99%
“…A Salmonella pan-genome microarray covering seven Salmonella genomes (Cooke et al, 2007) was used for this study. We also characterized these strains using other approaches, such as multilocus sequence typing (MLST) and PFGE.…”
Section: Introductionmentioning
confidence: 99%
“…Following ingestion of contaminated food/water, Salmonella in immunocompetent persons passes through the mucosa of the intestine and attaches to intestinal epithelia (Cooke et al, 2007). This is followed by invasion and intracellular replication of Salmonella, resulting in Salmonella containing vacuole (SCV).…”
Section: Pathogenesis Of Nts Infectionsmentioning
confidence: 99%
“…Salmonella infections continue to have a serious impact on human and animal health globally, causing significant morbidity and mortality with serious socioeconomic effects (Cooke et al, 2007). The World Health Organisation (WHO) estimated an annual incidence of 1.3 billion cases of diarrhea due to NTS, resulting in about 3 million deaths (Maripandi and Salamah, 2010).…”
Section: Epidemiology Of Human Non-typhoidal Salmonellosismentioning
confidence: 99%
“…Comparison of complete genomes have pointed out that the prophage content is one of the most important differences between genomes of Salmonella serovars, and specially among strains within a single serovar (McClelland et al, 2001;Parkhill et al, 2001;Porwollik et al, 2002;Porwollik et al, 2004;Thomson et al, 2004;Hermans et al, 2005;Cooke et al, 2007;Vernikos et al, 2007;Litrup et al, 2010). The detection of prophage sequences has been recently developed and proposed as a tool for the subtyping of strains (Hermans et al, 2006;Cooke et al, 2007).…”
Section: Phagementioning
confidence: 99%